Gastric acid suppression promotes alcoholic liver disease by inducing overgrowth of intestinal Enterococcus. Issue 1 (December 2017) - Llorente, Cristina; Jepsen, Peter; Inamine, Tatsuo; Wang, Lirui; Bluemel, Sena; Wang, Hui; Loomba, Rohit; Bajaj, Jasmohan; Schubert, Mitchell; Sikaroodi, Masoumeh; Gillevet, Patrick; Xu, Jun; et al.
Abstract Chronic liver disease is rising in western countries and liver cirrhosis is the 12th leading cause of death worldwide. Simultaneously, use of gastric acid suppressive medications is increasing. Here, we show that proton pump inhibitors promote progression of alcoholic liver disease, non-alcoholic fatty liver disease, and non-alcoholic steatohepatitis in mice by increasing numbers of intestinalEnterococcus spp. Translocating enterococci lead to hepatic inflammation and hepatocyte death. Expansion of intestinalEnterococcus faecalis is sufficient to exacerbate ethanol-induced liver disease in mice. Proton pump inhibitor use increases the risk of developing alcoholic liver disease among alcohol-dependent patients. Reduction of gastric acid secretion therefore appears to promote overgrowth of intestinalEnterococcus, which promotes liver disease, based on data from mouse models and humans. Recent increases in the use of gastric acid-suppressive medications might contribute to the increasing incidence of chronic liver disease. Proton pump inhibitors (PPIs) reduce gastric acid secretion and modulate gut microbiota composition. Here Llorenteet al . show that PPIs induce bacterial overgrowth of enterococci, which, in turn, exacerbate ethanol-induced liver disease both in mice and humans.